2002
DOI: 10.1055/s-2002-36197
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Transsphenoidal Approach: Outcome Analysis of 100 Consecutive Procedures

Abstract: The endoscopic endonasal transsphenoidal approach has been proposed in the past decade as a minimally invasive surgical technique for the removal of pituitary tumors. From January 1997 to November 1999, 100 consecutive patients with pituitary tumors underwent endoscopic endonasal surgery, according to Jho's technique. We employed 0 degrees, 30 degrees, 45 degrees, and 70 degrees rigid endoscopes, 18 - 30 cm in length, 4 mm in diameter with an outer sleeve for irrigation and secured to a holder. Among the 87 pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
171
1
31

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(215 citation statements)
references
References 15 publications
12
171
1
31
Order By: Relevance
“…Due to its recent introduction, there are only few reports describing larger series of patients with pituitary tumors operated via the endoscopic technique (25,29,35). It seems that the endocrine outcomes of the patients reported in these initial series are similar to those achieved by the conventional microscopic technique.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Due to its recent introduction, there are only few reports describing larger series of patients with pituitary tumors operated via the endoscopic technique (25,29,35). It seems that the endocrine outcomes of the patients reported in these initial series are similar to those achieved by the conventional microscopic technique.…”
Section: Discussionmentioning
confidence: 91%
“…It seems that the endocrine outcomes of the patients reported in these initial series are similar to those achieved by the conventional microscopic technique. Cappabianca et al (29) reported on 87 patients with various pituitary adenomas, including 8 patients with Cushing's disease, that were treated with endoscopic endonasal transsphenoidal pituitary surgery between 1997 and 1999. As remission criterion for patients with Cushing's disease the authors adopted a restoration of the circadian rhythm of cortisol together with the normalization of urinary cortisol levels.…”
Section: Discussionmentioning
confidence: 99%
“…9) The patients returned to daily activities within days of the operation because the endonasal endoscopic approach involves less pain and discomfort than the conventional approach. 1,9) We suggest that the endonasal endoscopic approach could be used to treat skull base lesions other than empty sella syndrome. 4) …”
Section: Discussionmentioning
confidence: 99%
“…The overall approach to the sella turcica was the same as that of endonasal endoscopic pituitary surgery. 1,9) Briefly, the sphenoethmoidal recess was approached under endoscopic vision, where the natural ostium of the sphenoid sinus was identified. The septal mucosa was cauterized 1 or 2 cm anterior to the ostium and the anterior wall of the sphenoid sinus was exposed on the same side.…”
Section: Operative Techniquementioning
confidence: 99%
“…Tem sido utilizado tanto para a remoção dos adenomas hipofisários como de craniofaringeomas e permite também correção cirúrgica de fístula liquórica. Vários autores que têm experimentado esta nova técnica demonstram resultados iguais ou superiores aos da cirurgia transefenoidal clássica com menor tempo de internação e menor desconforto pós-operatório (49)(50)(51).…”
Section: Novas Técnicas Utilizadasunclassified